Dichrorampha dinarica, new species, a century of confusion in European lepidopterology (Lepidoptera: Tortricidae) resolved by combining morphology and DNA barcoding - Huemer, Peter; Zlatkov, Boyan; Baixeras, Joaquin (Zootaxa, 2012)
Dichrorampha dinarica, new species, is described from the Dinaric mountains (Macedonia, Bosnia and Herzegovina). The newspecies was formerly confused with D. ligulana (Herrich-Schäffer, 1851) from the Alps and D. rilana Drenowsky, 1909 fromthe Rila mountains (Bulgaria). Therefore, a re-description of D. rilana is provided based on topotypical specimens. The diag-nostic morphological characters of the involved species, supported by significant divergence of the mtDNA barcode (COI fragment of 658 bp), are discussed in detail.